Higher Plasma Pyridoxal Phosphate Is Associated with Increased Antioxidant Enzyme Activities in Critically Ill Surgical Patients. (30th May 2013) - Cheng, Chien-Hsiang; Huang, Shih-Chien; Chiang, Ting-Yu; Wong, Yueching; Huang, Yi-Chia
Abstract : Critically ill patients experience severe stress, inflammation and clinical conditions which may increase the utilization and metabolic turnover of vitamin B-6 and may further increase their oxidative stress and compromise their antioxidant capacity. This study was conducted to examine the relationship between vitamin B-6 status (plasma and erythrocyte PLP) oxidative stress, and antioxidant capacities in critically ill surgical patients. Thirty-seven patients in surgical intensive care unit of Taichung Veterans General Hospital, Taiwan, were enrolled. The levels of plasma and erythrocyte PLP, serum malondialdehyde, total antioxidant capacity, and antioxidant enzyme activities (i.e., superoxide dismutase (SOD), glutathione S-transferase, and glutathione peroxidase) were determined on the 1st and 7th days of admission. Plasma PLP was positively associated with the mean SOD activity level on day 1 (r = 0.42, P < 0.05 ), day 7 (r = 0.37, P < 0.05 ), and on changes (Δ (day 7 − day 1)) (r = 0.56, P < 0.01 ) after adjusting for age, gender, and plasma C-reactive protein concentration. Higher plasma PLP could be an important contributing factor in the elevation of antioxidant enzyme activity in critically ill surgical patients.